(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
From the Religious Disenchantment of Christian Integrity to the Modern and Post-Modern Religious Re-enchantment. A few Considerations from the Orthodox Point of View. Our study aims to capture and evaluate the dissolving consequences of secularizing/secularizing factors, factors that have influneced and determined the freedom of conscience and choice of the recently religious man1, by moving from the unraveling of Christian integrity to modern and postmodern religious revival. From this perspective, we will insist on those aggravating circumstances in which the consequences of globalizing religious political-economic-financial and philosophical-social factors have generated and fueled the regressive course of faith, by fragmenting and compromising moral moral integrity, modern society and post- modern that tries to relate to a certain God and to a certain morality, starting from a horizontal/flattening vision with a soteriological and eschatological future as uncertain and distant as possible. Taking into account all these implications, of a derogatory religious nature, we aim to approach the new reality of the present times that we seek to understand and describe, delimiting the profiles of the current situation of religious crisis, assuming, from this point of view, the analytical perspective that Orthodox theology generously provides us with.